THE EFFECT OF PRICE, PRODUCT, AND PHYSICAL EVIDENCE ON CONSUMERS’ PURCHASE DECISIONS AT MIE GACOAN JEMBER REGENCY - Aminullah, Adimas Ilham; Wardhani, Roro Aditya Novi; Hapsari, Yusita Titi (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2026)
Introduction: The rapid expansion of Indonesia’s fast-food sector has intensified market competition, prompting brands to identify the key drivers of consumer buying behavior. This research investigates how price, product quality, and physical evidence influence consumer purchasing decisions at Mie Gacoan, Jember Branch. The study specifically seeks to assess how each of these variables, both individually and collectively, affects the purchasing behavior of young consumers, who are primarily comprised of students and university-level respondents.Methods: This study adopted a quantitative field research Design, drawing on primary data obtained from 160 respondents selected through purposive sampling. The gathered data were analyzed using multiple linear regression techniques, aided by statistical software to evaluate both the individual (partial) and combined (simultaneous) influences of the examined variables.Results: The results of this study reveal that the three independent variables have a positive and significant impact on consumer purchasing decisions, with product quality identified as the most influential factor. An Adjusted R^2 value of 0.617 indicates that about 61.7% of the variance in purchase decisions is explained by these variables. In contrast, the remaining 38.3% is attributed to other determinants beyond the scope of this model.Conclusion and suggestion: The study concludes that the combination of competitive pricing, high product quality, and appealing physical evidence is the key determinant shaping purchase decisions among young consumers. The practical implications of this research highlight the importance of implementing marketing strategies that prioritize product quality and customer experience to sustain consumer loyalty and strengthen the brand’s competitive position in the fast-food industry. Keywords: Mie Gacoan, Physical Evidence, Price, Product Quality, Purchase Decision